Smart distribution communication network planning strategy based on optimal cost and network load - Yirong WANG; Yanru WANG; Yanhua HE; Yonghui WANG; Liangrui TANG (Dianxin kexue)
Considering of the characteristics such as small amount data of single communication terminal node and large scale distribution of terminal nodes,the strategy of network planning should increase the number of access nodes and maximize the capacity of the network.In the macro and micro base station deployment,the macro base station and the micro base station were simultaneously deployed to provide more deployment options for the micro base station.Based on the analysis of the demand of smart distribution network communication services and the drawbacks of the existing network planning,a multi-objective optimization model was established and a single objective optimization model was established for comparative analysis.Finally,the superiority of the strategy was proved from the scheme diagram and network performance analysis.